Pruritus und Psoriasis - Weisshaar, Elke (Der Hautarzt, 2012)
Pruritus is a frequent but often unrecognized and underestimated symptom in patients with psoriasis. The underreporting may be due to lower frequency and reduced intensity of pruritus compared to other pruritic diseases such as atopic eczema or uremic pruritus, as well as impairment of psychosocial well-being caused by e.g. depression, social withdraw and secretiveness. Recent studies show pruritus being more prevalent in psoriasis, especially plaque-type psoriasis, than previously believed and severely affecting patients’ quality of life. The assessment of pruritus and its associated effects is a significant component of clinical management of psoriasis. The presented suggest we should not underestimate pruritus in psoriasis and must consider this symptom in planning therapy.
Gesehen am 09.05.2019